1363 'FRAILTY AS AN ADJECTIVE RATHER THAN A DIAGNOSIS' - THE IDENTIFICATION OF FRAILTY IN PRIMARY CARE: A QUALITATIVE INTERVIEW STUDY. (16th January 2023) - Seeley, A; Glogowska, M; Hayward, G
Abstract: Introduction: In 2017 NHS England introduced proactive identification of frailty into the General Practitioners (GPs) Contract. There is currently little information as to how this policy has been operationalised by front-line clinicians, their working understanding of frailty, or perceptions of impact on patient care. Evidence from international settings suggests primary care clinicians may have mixed interpretations of frailty, with important implications for their willingness to support different frailty interventions. We aimed to explore the conceptualisation of frailty, and how community-dwelling frail older adults are identified in primary care. Methods: Semi-structured interviews were conducted with primary care staff across England, including GPs, physician associates, nurse practitioners, paramedics and pharmacists. Thematic analysis was facilitated through NVivo (Version 13). Results: 31 practitioners participated (12 GPs, 19 non-GPs). Frailty was seen as difficult to define, with uncertainty in its value as a medical diagnosis. The most common working model was the frailty phenotype, associated with deterioration at end of life. There was a mixture of formal and informal processes for identifying frailty. A few practices had embedded population screening and structured reviews. Informal processes included use of 'housebound' as a proxy for frailty, identification through chronic disease and medication reviews, and holistic assessment through good continuity of care. Many clinicians described poor accuracy of the electronic Frailty Index, yet it was commonly used to grade frailty during protocolised chronic disease reviews. The Clinical Frailty Score, in contrast, was felt to be easy to use and interpret, but inconsistently recorded within electronic health records. Most clinicians favoured better tools for identifying frailty, alongside resources to support these individuals. Conclusions: Concepts of frailty in primary care differ. Identification is predominantly ad-hoc, opportunistic and associated with terminal illness. A more cohesive approach to frailty, relevant to primary care, together with better diagnostic tools, may encourage wider recognition.